2004
DOI: 10.1128/jb.186.21.7312-7326.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nutrient-Induced Dispersion in Pseudomonas aeruginosa PAO1 Biofilm

Abstract: The processes associated with early events in biofilm formation have become a major research focus over the past several years. Events associated with dispersion of cells from late stage biofilms have, however, received little attention. We demonstrate here that dispersal of Pseudomonas aeruginosa PAO1 from biofilms is inducible by a sudden increase in carbon substrate availability. Most efficient at inducing dispersal were sudden increases in availability of succinate > glutamate > glucose that led to ϳ80% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
421
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(443 citation statements)
references
References 67 publications
(101 reference statements)
20
421
0
2
Order By: Relevance
“…2). We showed that dispersed cells are in a distinct stage in the transition from biofilm to planktonic lifestyle, as supported by the evidence showing that biofilm cells differ from dispersed cells 15 . We identified multiple T2SS genes, such as PA3820 (secF) and PA3821 (secD), that were Pyoverdine RFU/OD600 Pyoverdine RFU/OD600…”
Section: Dispersed Cells Represent a Distinct Stage Of Bacterial Lifesupporting
confidence: 55%
See 1 more Smart Citation
“…2). We showed that dispersed cells are in a distinct stage in the transition from biofilm to planktonic lifestyle, as supported by the evidence showing that biofilm cells differ from dispersed cells 15 . We identified multiple T2SS genes, such as PA3820 (secF) and PA3821 (secD), that were Pyoverdine RFU/OD600 Pyoverdine RFU/OD600…”
Section: Dispersed Cells Represent a Distinct Stage Of Bacterial Lifesupporting
confidence: 55%
“…The active process of dispersing cells is specific and regulated, in contrast to mechanical and passive dispersal, which involves sloughing off biofilm cells. While it is common knowledge that biofilm cells differ from dispersed cells 15 , it is unclear whether biofilm-dispersed cells are similar to planktonic cells with respect to their physiology.…”
mentioning
confidence: 99%
“…Biofilm dispersion can be induced by a variety of environmental cues, including changes in growth medium composition, pH, oxygen, and carbon concentrations, exposure to heavy metals and nitric oxide, exposure to the polysaccharide degrading enzyme dispersin B, and self-synthesized signaling molecules such as cis-2-decenoic acid (1)(2)(3)(4)(5)(6)(7)(8)(9). Dispersed cells are characterized by distinct gene expression and protein production patterns and increased susceptibility to antimicrobial agents compared with their sessile counterparts (2,(10)(11)(12). Moreover, although biofilms are considered the root cause of chronic and persistent infections (13), biofilm dispersion may be part of an inherent strategy of Pseudomonas aeruginosa to initiate a disseminating phenotype, causing acute and periodic infections.…”
mentioning
confidence: 99%
“…Regulation of biofilm dispersion has also been linked to the modulation of the intracellular signaling molecule cyclic di-GMP (c-di-GMP), high levels of which promote sessile growth, and low levels correlate with planktonic existence. Several proteins associated with dispersion have been shown to possess cdi-GMP-modulating activity (1)(2)(3)(4)14). These include the phosphodiesterases (PDEs) RbdA and DipA, which promote the return to free-swimming growth by reducing cellular c-di-GMP levels (15,16).…”
mentioning
confidence: 99%
“…[17][18][19] Furthermore, modulation of c-di-GMP signaling by environmental changes has also been linked with the dispersion of cells from established biofilms. [20][21][22] Therefore, drugs able to inhibit c-di-GMP synthesis are promising candidates for new anti-microbial agents with anti-biofilm activity. Indeed, genetic manipulation of c-di-GMP levels through the modulation of PDE activity in P. aeruginosa prevented and promoted clearance of biofilm infections in mice.…”
Section: Introductionmentioning
confidence: 99%